Evaluation of Corrosion Behavior of Copper in Chloride Media Using Electrochemical Impedance Spectroscopy (EIS) - Nagiub,A.M. (2005)
The corrosion behavior of pure copper rotating cylinder electrode (RCE) exposed to 3% NaCl or artificial seawater prepared as Vätäänen nine salt solution (VNSS) has been studied using electrochemical impedance spectroscopy (EIS) and polarization techniques. EIS experiments for copper RCE were carried out at different rotation rate from 0 rpm to 1600 rpm. Polarization resistance (Rp) values were obtained from both EIS and polarization experiments. Excellent agreement between impedance and polarization data is observed. RCE experiments demonstrated that Ecorr and corrosion rate for copper depend linearly on rotation speed r0.7. The results obtained showed that EIS is a powerful electrochemical method to follow the change of corrosion mechanisms.